Improvement of the method for determining the resistance to inhaling cigarettes and pressure overfall of filter sticks considering international requirements - E. V. Gnuchikh; N. P. Samoilenko; I. G. Kandashkina; E. Y. Smirnova (Новые технологии)
Resistance to inhaling and pressure overfall of filter sticks are of great importance for the manufacture of tobacco products with the specified parameters of quality and safety. Methods for determining these indicators, devices for their measurement are constantly improved. In this regard, an interstate standard is being developed according to ISO 6565: 2015 version in order to update and comply with international requirements when testing tobacco products, which, after adoption, will be used by testing laboratories in preparing cigarettes for analytical definitions during machine smoking.